2016
DOI: 10.1055/s-0036-1580727
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Infected Facial Implants

Abstract: Alloplastic facial implants have a wide range of uses to achieve the appropriate facial contour. A variety of materials such as metals, polymers, ceramics and synthetic injectable fillers are available to the reconstructive and aesthetic surgeon. Besides choosing the right surgical technique and the adequate material, the surgeon must be prepared to treat complications. Infection is an uncommon but serious complication that can cause displeasing consequences for the patient. There are few references in literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This inconsistency could be potentially explained by our finding that all 3 implant types demonstrate similarly low rates of these particular complications, which suggest that implant selection may not actually have an appreciable effect on clinical outcomes. In fact, prior studies have demonstrated that with regard to infections, other factors such as location of implantation 16 and preoperative implant biofilm seeding 18 may be more influential than the implant itself.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency could be potentially explained by our finding that all 3 implant types demonstrate similarly low rates of these particular complications, which suggest that implant selection may not actually have an appreciable effect on clinical outcomes. In fact, prior studies have demonstrated that with regard to infections, other factors such as location of implantation 16 and preoperative implant biofilm seeding 18 may be more influential than the implant itself.…”
Section: Discussionmentioning
confidence: 99%
“…Although the customary treatment of implant-related infections previously looked towards prospective removal of the foreign body, conservative alternatives have more recently been favored. Such alternatives include wound debridement and localized delivery of targeted antibiotic therapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…A highly polished surface may discourage periosteum reattachment, whereas a very rough surface may encourage bacterial growth when contamination with saliva occurs. [ 15 ]…”
Section: Methodsmentioning
confidence: 99%